AZYUMARDI AZRA’S THOUGHT ON MULTICULTURAL EDUCATION - Idris, Muh (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2020)
Abstract: Islamic religious education is often accused of advocating religious fanaticism and ideology of truth. The condition is resulted from relative detachment of religious education from social reality. As such, religious education fails to strengthen the awareness of religious plurality in the society. This paper is the result of a Content Analysis research on Azyumardi Azra’s thoughts on multicultural education. It is found that according to Azyumardi Azra, multicultural education is an education of and for socio-cultural diversity aiming at strengthening the Indonesian unity amid its very diverse population. Unity in Diversity is one of the four pillars of Indonesian nationhood namely the Pancasila, NKRI, 1945 Constitution, and Unity in Diversity.Keywords: education, multiculturalism, Azyumardi Azra, fanatism